On the expansion of solutions to differential equations with discontinuous right-hand side in a series in initial data and parameters - Akhmetov, M. U. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The conditions under which the solutions of equations with discontinuous right-hand sides depend on the initial data and parameters analytically are investigated. A definition is introduced, which specifies this dependence in the case where a surface of discontinuity exists.